2015
DOI: 10.1371/journal.pone.0123274
|View full text |Cite
|
Sign up to set email alerts
|

Medically Unexplained and Explained Physical Symptoms in the General Population: Association with Prevalent and Incident Mental Disorders

Abstract: BackgroundClinical studies have shown that Medically Unexplained Symptoms (MUS) are related to common mental disorders. It is unknown how often common mental disorders occur in subjects who have explained physical symptoms (PHY), MUS or both, in the general population, what the incidence rates are, and whether there is a difference between PHY and MUS in this respect.AimTo study the prevalence and incidence rates of mood, anxiety and substance use disorders in groups with PHY, MUS and combined MUS and PHY comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 57 publications
(59 reference statements)
1
29
1
Order By: Relevance
“…All definitions in Table 1 were predefined, and as strict as possible defined to support unambiguous interpretation. Definitions are in line with previously published papers using data from NEMESIS-2 (33,53). Given that the data had already been collected by independent researchers, results could not be influenced by the authors.…”
Section: Biasmentioning
confidence: 71%
“…All definitions in Table 1 were predefined, and as strict as possible defined to support unambiguous interpretation. Definitions are in line with previously published papers using data from NEMESIS-2 (33,53). Given that the data had already been collected by independent researchers, results could not be influenced by the authors.…”
Section: Biasmentioning
confidence: 71%
“…CBT is recommended in the Dutch multidisciplinary guideline for MUS and somatoform disorders and can be offered by the GP or in the specialized mental health care, if the GP considers the patient to be too complex or when the patient–doctor relationship is perturbed 40. In addition to the CBT for MUS and somatoform disorder, specialist psychiatric attention may be required for other mental health problems associated with physical symptoms (unexplained or explained) 2,42. Given that all people with physical symptoms (explained or unexplained) show more entry into primary care, but only people with MUS show more entry into specialized mental health care, MUS is apparently of higher influence than explained physical symptoms on the decision of the GP whether or not to refer to specialized mental health care.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with chronic medical conditions frequently suffer from comorbid depression or anxiety disorders [13][14][15][16][17]. This comorbidity can easily lead to disability, such as in the workplace [18,19], and high health care costs [20].…”
Section: Protocol Registration Numbermentioning
confidence: 99%
“…Therefore, we cannot draw conclusions about this. This is an interesting subject for further research, because the combination of anxiety disorders and chronic medical conditions is highly prevalent [13,93]; the presence of an anxiety disorder leads to a higher likelihood of disability in chronic medical conditions [15], and a more negative perception of the influence of the chronic medical condition [94]. It has also been suggested that the presence of physical symptoms negatively influences the course of the anxiety disorder [22].…”
Section: Limitationsmentioning
confidence: 99%